Staffing patterns of student assistants in twenty-five selected academic libraries in Metro Manila - Leonardo, Rapunzel V.; Dizon, Leticia B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1999)
The general purpose of this study is to determine the staffing patterns of student assistants in twenty-five selected academic libraries in Metro Manila. The survey method was used in the study. A total of 175 student assistants and 93 librarians responded to the structured questionnaires developed by the researcher.
The study: determined the profile of students assistants with regard to age, sex, year level, course length of service and rate of payment; 2) described the qualifications required for student assistants' work; 3) identified the methods used in selecting student assistants; 4) found out the motivation of students in working as student assistants; 5) ascertained the activities performed by student assistants; 6) pointed out the concerns and issues as regards staffing student assistants.
The findings of the study are: 1) Majority (71.4 percent) of student assistants are female; 2) More than half (66.3 percent) of student assistants are in the age group of 17 to 19 years old; 3) Majority (61.7 percent) of student assistants are sophomores and juniors; 4) There is a scarcity (6.3 percent) of Library science student assistants in academic libraries; 5) Most (22.3 percent) of the student assistants are assigned in the Circulation Section; 6) One hundred (100) hours per month is the usual length of service of student assistants; 7) Majority of student assistants work on a scholarship basis; 8)Ability to take responsibility (90.3 percent) is the number one qualification required for student assistants work; 9) Interview (80.6 percent) is the primary method in selecting student assistants; 10) Most (71.0 percent) of the academic libraries administer training of student assistants; 11) There are a number of benefits and problems encountered in employing student assistants; 12)Work experience (97.0 percent) is the top motivation among student assistants; 13) shelving of books (85.7 percent) is the activity performed by almost all student assistants; 14) Majority of student assistants have positive personal experience while working with their respective libraries; and 15) Almost all student assistants are satisfied with their work in the library.
In general, student assistants obviously present a large component of library staffing in academic libraries in Metro Manila. They usually exceed full-time non-professional staff number.
Computer print out.
Vita.
Thesis (Bachelor of Library Science)--University of the Philippines Diliman
Keywords: Student library assistants -- Philippines -- Manila Metropolitan Area; Academic libraries -- Philipines -- Manila Metropolitan Area